Habits of Mind of Indonesian Students in Kota Kinabalu, Sabah, Malaysia: A Survey Study Through Biology Education - Ria Yulia Gloria; Egina Bumiarti; Deka Andriani (Eduscape : Journal of Education Insight, 2026)
This study examines students’ thinking habits in biology learning at the Indonesian School in Kota Kinabalu, Sabah, Malaysia. The novelty of this research lies in its focus on analyzing thinking habits within the context of an Indonesian school abroad, which remains underexplored. The study employed a quantitative descriptive survey design involving 165 students from various grade levels. Data were collected using a questionnaire based on the Thinking Habits framework developed by Arthur L. Costa and Bena Kallick, consisting of 16 items measured on a scale ranging from very weak (0–20), weak (21–40), moderate (41–60), strong (61–80), to very strong (81–100). The collected data were analyzed using descriptive statistical techniques to determine the distribution and average scores of each thinking habit aspect. The results showed that 82.42% of students were categorized as having strong thinking habits, 13.30% as very strong, and 4.24% as moderate. The highest average score was found in the aspect of responding with curiosity and wonderment, while thinking flexibly and metacognition showed relatively lower average scores. These findings provide insights into the profile of students’ thinking habits in an international educational context and highlight areas that require further development.